Hoxb3 Regulates Jag1 Expression in Pharyngeal Epithelium and Affects Interaction With Neural Crest Cells - Zhang, Haoran; Xie, Junjie; So, Karl Kam Hei; Tong, Ka Kui; Sae-Pang, Jearn Jang; Wang, Li; Tsang, Sze Lan; Chan, Wood Yee; Wong, Elaine Yee Man; Sham, Mai Har (Frontiers in Physiology, 2021)
Craniofacial morphogenesis depends on proper migration of neural crest cells and their interactions with placodes and other cell types. Hox genes provide positional information and are important in patterning the neural crest and pharyngeal arches (PAs) for coordinated formation of craniofacial structures. Hox genes are expressed in the surface ectoderm and epibranchial placodes, their roles in the pharyngeal epithelium and their downstream targets in regulating PA morphogenesis have not been established. We altered the Hox code in the pharyngeal region of the Hoxb3Tg/+ mutant, in which Hoxb3 is driven to ectopically expressed in Hoxb2 domain in the second pharyngeal arch (PA2). In the transgenic mutant, ectopic Hoxb3 expression was restricted to the surface ectoderm, including the proximal epibranchial placodal region and the distal pharyngeal epithelium. The Hoxb3Tg/+ mutants displayed hypoplasia of PA2, multiple neural crest-derived facial skeletal and nerve defects. Interestingly, we found that in the Hoxb3Tg/+ mutant, expression of the Notch ligand Jag1 was specifically upregulated in the ectodermal pharyngeal epithelial cells of PA2. By molecular experiments, we demonstrated that Hoxb3 could bind to an upstream genomic site S2 and directly regulate Jag1 expression. In the Hoxb3Tg/+ mutant, elevated expression of Jag1 in the pharyngeal epithelium led to abnormal cellular interaction and deficiency of neural crest cells migrating into PA2. In summary, we showed that Hoxb3 regulates Jag1 expression and proposed a model of pharyngeal epithelium and neural crest interaction during pharyngeal arch development.